Plan de negocio para la comercialización y exportación de rosas a Estados Unidos. - Maigua Tiglla, Julio Francisco (2023)
This project entitled "Business plan for the marketing and export of roses to the United States." had as its objective; Investigate the environment in which Ecuadorian floriculture operates in the United States market; Develop strategies that allow the company to enter foreign markets according to required standards and regulations; Carry out an administrative, operational and financial study to determine the feasibility of the project. The applied methodology was based on a quantitative approach of descriptive type that allowed to determine the population and the sample of the study; exploratory that support in data collection; and the observation that was of vital importance in the processes involved in the export of roses; Secondary information of a bibliographical type was used to determine the levels of demand, tastes and preferences of the clients of the state of Florida and interviews were carried out with the representatives of the department of foreign trade located in the Province of Cotopaxi and the feasibility of the project was determined. with a VAN USD 144,051.88 and an IRR of 55% greater than the opportunity cost (55% > 19.19%), which reflected positive results.